2017
DOI: 10.1002/jbmr.3102
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Increases in Trans Persons After 1 Year of Hormonal Treatment: A Multicenter Prospective Observational Study

Abstract: Sex steroids are important determinants of bone acquisition and bone homeostasis. Cross-sex hormonal treatment (CHT) in transgender persons can affect bone mineral density (BMD). The aim of this study was to investigate in a prospective observational multicenter study the first-year effects of CHT on BMD in transgender persons. A total of 231 transwomen and 199 transmen were included who completed the first year of CHT. Transwomen were treated with cyproterone acetate and oral or transdermal estradiol; transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 29 publications
6
81
0
2
Order By: Relevance
“…In transwomen, no differences in change in LS BMD between age groups were present, whereas in transmen LS BMD increased more in the oldest age group (≥40 years) compared with younger age groups. This finding was also described in a prospective 1‐year follow‐up study . In the current study, we found that the increase continued after 1 year.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In transwomen, no differences in change in LS BMD between age groups were present, whereas in transmen LS BMD increased more in the oldest age group (≥40 years) compared with younger age groups. This finding was also described in a prospective 1‐year follow‐up study . In the current study, we found that the increase continued after 1 year.…”
Section: Discussionsupporting
confidence: 91%
“…Gender‐affirming hormonal treatment (HT) in transgender people influences bone metabolism. After 1 year of HT the BMD increases in transwomen (male‐to‐female transgender people), whereas in transmen (female‐to‐male transgender people) a maintenance or increase in BMD is described. More specifically, a larger increase in BMD was found in postmenopausal transmen with estrogen deficiency prior to HT compared with premenopausal transmen with normal estradiol concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies found either a maintenance (16)(17)(18)(19)(20) or increase (16)(17)(18)(21)(22)(23)(24)(25)(26) in BMD in both adult trans women and trans men after short-term HT. Earlier studies found either a maintenance (16)(17)(18)(19)(20) or increase (16)(17)(18)(21)(22)(23)(24)(25)(26) in BMD in both adult trans women and trans men after short-term HT.…”
Section: Introductionmentioning
confidence: 92%
“…Sex steroids are important determinants of bone acquisition and bone homeostasis. In men, testosterone stimulates the process of periosteal apposition during puberty, producing a greater cortical bone size and wider bones as compared to women . Male to female transsexual individuals (transwomen) undergo oestrogen therapy associated or not with anti‐androgens, reducing endogenous testosterone and inducing feminization.…”
Section: Introductionmentioning
confidence: 99%